Quality competition or quality cooperation? License-type and the strategic nature of open source vs. closed source business models - Sebastian von Engelhardt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
In the ICT sector, product-software is an important factor for the quality of the products (e.g. cell phones). In this context, open source software enables firms to avoid quality competition as they can cooperate on quality without an explicit contract. The economics of open source (OS) versus closed source (CS) business models are analyzed in a general two- stage model that combines aspects of non-cooperative R&D with the theory of differentiated oligopolies: In stage one, firms develop software, either as OS or CS, or as a an OS-CS-mix if the license allows. In stage two, firms bundle this with complementary products and compete à la Cournot. The model allows for horizontal product differentiation in stage two. The finding are: 1.) While CS-decisions are always strategic substitutes, OS-decisions can be strategic complements. Furthermore, CS is a strategic substitute to OS and vice versa. 2.) The type of OS-license plays a crucial role: only if the license prohibits a direct OS-CS code mix (like the GPL), then Nash-equilibria with firms producing OS code exist for all parameters. 3.) In the equilibrium of a mixed industry with restricted licenses, OS-firms offer lower quality than their CS-rivals.
Keywords: D43; L17; O34; 330; open source; commercial open source; Cournot; R&D; Softwareindustrie; Oligopol; Lizenzvergabe; Open Source; Produktdifferenzierung; Wettbewerb; Produktqualität; Theorie